Cyrtodactylus panitvongi, a new cave-dwelling Bent-toed Gecko from Lopburi Province, central Thailand (Squamata: Gekkonidae) - Pauwels, Olivier S. G.; Chotjuckdikul, Natthaphat; Donbundit, Nattasuda; Sumontha, Montri; Meesook, Worawitoo (Zootaxa, 2024)
We describe Cyrtodactylus panitvongi sp. nov. from Tham Khao Chan (14°58’42.2”N 101°18’40.6”E), a limestone cave in Lopburi Province, central Thailand. The new species is characterized by the following combination of morphological characters and pattern: maximal known snout-vent length of 85 mm, 15–18 interorbital scales, 35–37 interciliary scales, 10–12 supralabials, 9–11 infralabials, 29–33 paravertebral tubercles of which 22–25 between limb insertions, 18 longitudinal rows of dorsal tubercles at midbody, 40–42 ventral scale rows at midbody, poorly defined, non-denticulate ventrolateral folds, a series of 13 or 14 enlarged femoroprecloacal scales including 2 pores on the proximalmost scales on each side separated by a single smaller medial scale in males, or six precloacal pits on a continuous series of 32–34 enlarged femoroprecloacal scales in females, no precloacal groove or depression, two or three postcloacal spurs on each side of the base of the tail in males and females, no interdigital webbing, 16–19 total subdigital lamellae on 4th toe, a row of widened median subcaudal plates, a banded dorsal pattern including an uninterrupted nuchal collar and three dark bands on dorsum, 10 or 11 dark-colored rings on original tail, and a golden iris. This trogloxene species is added to a long list of squamates endemic to the Saraburi Group Limestones.